Right to compensation for damage caused by data processing: international issues - Miguel Asensio, Pedro Alberto de (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The recent judgments of the Court of Justice on Article 82 GDPR provide insight into the requirements of this right to compensation. They are also illustrative of the limits of the GDPR as an instrument of harmonization, e.g. as regards the assessment of the amount of compensation. This contribution addresses the specific elements of uncertainty that arise with regard to compensation claims in cross-border situations. The significance of the provisions on jurisdiction of Article 79 GDPR and their interplay with other rules are discussed. In addition, the contribution addresses the complex choice of law issues that arise in connection to the limits of the harmonization brought about by the GDPR in this area.